Cinchona anderssonii (Rubiaceae), a new overlooked species from Bolivia - Maldonado, Carla; Persson, Claes; Alban, Joaquina; Antonelli, Alexandre; Rønsted, Nina (Phytotaxa, 2017)
Cinchona anderssonii, a new species from the Yungas forests of the Andes in Bolivia, is described and illustrated. It is unique in Cinchona by having the combination of elliptic leaf blades glossy above, distinct circular pit domatia at secondary vein axils, basipetally dehiscent capsules, and relatively large seeds (8–11 mm long). A taxonomic key for the identification of the Cinchona species occurring in Bolivia is presented.